Prediction of Responsiveness of Gait Variables to Rehabilitation Training in Parkinson's Disease - Serrao, Mariano; Chini, Giorgia; Caramanico, Guido; Bartolo, Michelangelo; Castiglia, Stefano Filippo; Ranavolo, Alberto; Conte, Carmela; Venditto, Teresa; Coppola, Gianluca; di Lorenzo, Cherubino; Cardinali, Patrizio; Pierelli, Francesco (Frontiers in Neurology, 2019)
Background: Gait disorders represent one of the most disabling features of Parkinson’s disease, which may benefit from rehabilitation. No consistent evidence exists about which gait biomechanical factors can be modified by rehabilitation and which clinical characteristic can predict rehabilitation-induced improvements. Objectives: The aims of the study were as follows: i) to recognize the gait parameters modifiable by a short-term rehabilitation program; ii) to evaluate the gait parameters that can normalize after rehabilitation; and iii) to identify clinical variables predicting improvements in gait function after rehabilitation. Methods: Thirty-six patients affected by idiopathic Parkinson’s disease in Hoehn-Yahr stage 1-3 and 22 healthy controls were included in the study. Both clinical and instrumental (gait analysis) evaluations were performed before and after a 10-week rehabilitation treatment. Time-distance parameters, lower limb joint, and trunk kinematics were measured. Results: At baseline evaluation with matched speed, almost all gait parameters were significantly different between patients and healthy controls. After the 10-week rehabilitation, most gait parameters improved, and spatial asymmetry and trunk rotation normalized. Multiple linear regression of gender combined with Unified Parkinson’s Disease Rating Scale-III predicted both ΔSpeed and ΔStep length of both sides; gender combined with Unified Parkinson’s Disease Rating Scale-II predicted ΔCadence; age combined with Hoehn-Yahr score and disease duration predicted Δtrunk rotation range of motion. Conclusions: Impaired gait parameters are susceptible to improvement by rehabilitation, and younger men with Parkinson’s disease who are less severely affected and at early disease stage are more susceptible to improvements in gait function after a 10-week rehabilitation program.